Common Childhood Diseases (IntechOpen, 2025)
Along with remarkable improvements in prevention, diagnostics, and medical care, common diseases of childhood have evolved considerably. Preventable childhood diseases have declined remarkably in newborns, young children, and adolescents because of scientific and medical discoveries in vaccine and drug development, newborn diagnostic screening, genetics, and genomics. Varied imaging, telemonitoring, and interventional technologies have been successfully implemented to detect early and treat effectively childhood diseases that traditionally had been thought of as devastating and deadly. Along with these, changes in environment, urbanization and pollution, sedentary lifestyles, and overload of the Internet and social media have impacted the health and wellbeing of our children, gradually increasing the prevalence and morbidity of obesity, drug-resistant infections, cancer, neurological conditions, and autism spectrum disorders in the pediatric population. This book explores select neurological, hematological, rheumatological, and nephrological diseases that we editors consider to have substantially evolved over the past decades.